2010
DOI: 10.1136/bjo.2009.173120
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy combined with ranibizumab for polypoidal choroidal vasculopathy: results of a 1-year preliminary study

Abstract: Background/aims To determine the potential efficacy and safety of combined verteporfin photodynamic therapy (PDT) with ranibizumab for the treatment of polypoidal choroidal vasculopathy (PCV). Methods In this prospective, non-comparative, interventional study, 12 eyes from 12 patients that had active PCV were treated with PDT combined with three monthly intravitreal injections of ranibizumab. The patients were then monitored monthly with measurements of best-corrected visual acuity (BCVA) and central retinal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…The reports of greater expression of VEGF in histopathology and increased VEGF in the aqueous humor have suggested the association of PCV and VEGF [16,17]. Some of the reports present that the anti-VEGF treatment might be a potential treatment to improve PCV [19,20,21,22,23,24,27]. Conversely, in terms of the polyp regression rate, anti-VEGF monotherapy could be inferior to PDT monotherapy or intravitreal anti-VEGF treatment combined with PDT [19,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reports of greater expression of VEGF in histopathology and increased VEGF in the aqueous humor have suggested the association of PCV and VEGF [16,17]. Some of the reports present that the anti-VEGF treatment might be a potential treatment to improve PCV [19,20,21,22,23,24,27]. Conversely, in terms of the polyp regression rate, anti-VEGF monotherapy could be inferior to PDT monotherapy or intravitreal anti-VEGF treatment combined with PDT [19,27].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reports present that the anti-VEGF treatment might be a potential treatment to improve PCV [19,20,21,22,23,24,27]. Conversely, in terms of the polyp regression rate, anti-VEGF monotherapy could be inferior to PDT monotherapy or intravitreal anti-VEGF treatment combined with PDT [19,27]. The previous study indicated that eyes with a cluster of grapes-like polypoidal dilatations of the vessels had a high risk for severe visual loss [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although combined therapy with PDT and anti-VEGF agents has been reported in patients with neovascular age-related macular degeneration [25,26,27,28,29], there are few reports of combination therapy for PCV [30,31]. The purpose of the present study was to evaluate the results of combination therapy with PDT and intravitreal anti-VEGF injection in PCV patients.…”
Section: Introductionmentioning
confidence: 99%